COMPOSITION OF ELEMENTS OF WINTER GARLIC (ALLIUM SATIVUM L.) - T. M. Seredin; A. F. Agafonov; L. I. Gerasimova; L. V. Krivenkov (Овощи России, 2015)
Ten varieties of winter garlic were tested for ability to accumulate macroand microelements. Genotype dependence was revealed. The most valuable varieties Strelets, Odintsovskiy Yubileyniy, Podnebesniy, Zaokskiy, and Replikant are characterized by high yield and content of macro- and microelements. The varieties Zaokskiy and Strelets are recommended for next breeding program as an initial breeding material.